Comparison of surgical outcomes of Ultrasonic technique (Harmonic Focus™) with Conventional technique in open hemithyroidectomy - Regmi, Deepak; KC, Toran; Bista, Meera; Shrestha, Sangita (Journal of Kathmandu Medical College, 2014)
Background: The option for dissection and haemostasis during thyroid surgery include either the modern ultrasonic technology (Harmonic Focus™) or the conventional technique using knot and ties, monopolar or bipolar electrocautery. Comparison between the surgical outcomes of open hemithyroidectomy using these two modalities was done. Objective: To compare the surgical outcomes of ultrasonic technique using Harmonic Focus™ (HS) with Conventional technique (CT) in open hemithyoidectomy. Method: Twenty consecutive patients undergoing open hemithyroidectomy for benign solitary thyroid nodule of ≤ 3 cm were randomly assigned into two groups; group HS (n=10) and group CT (n=10). Analysis of surgical outcomes performed by these two techniques, particularly: operative time, intra-operative blood loss, post operative pain, incision size, complications and hospital stay were done. Results: The age, sex and pathologies were comparable in both the groups. For the group HS, mean operative time was (mean ± SD=55 ± 5 min) 15 minutes shorter than group CT (mean ± SD= 70 ± 10 min) (P<0.01). Mean operative blood loss was (mean ± SD=20 ±10 ml) 16 ml less in group HS than CT (mean ± SD= 36 ±12 ml) (P<0.01). The group HS experienced less post operative pain (mean ± SD=4 ± 0.94 VAS) than CT (mean ± SD= 7 ± 0.81 VAS) (P<0.001). The incision size at the time of skin closure was 1.6 cm shorter in group HS ((mean ± SD= 3.95 ±0.61 vs. 5.5 ± 0.78cm) (P<0.01). Hospital stay (mean ± SD= 2.30 ± 0.48 vs. 4.20 ±0.42 days) was statistically significant (P<0.01) in group HS than CT. There were no major complications. Conclusion: In patients undergoing open hemithyroidectomy, HS is a faster, better cosmetic, safe and less morbid tool than CT. Its use reduces operative time, blood loss, post operative pain, scar size, along with hospital stay. DOI: http://dx.doi.org/10.3126/jkmc.v2i4.11774 Journal of Kathmandu Medical College Vol. 2, No. 4, Issue 6, Oct.-Dec., 2013 Page: 175-180